The behaviour of the streak-breasted bulbul Ixos siquijorensis siquijorensis on Siquijor Island, Philippines - Bucol, Abner A. (2008)
This paper describes some feeding habits, vocalizations, visual displays, roosting, aggression, bathing and preening, as well as the nest and eggs of the endangered Siquijor Streak-breasted Bulbul (Ixos siquijorensis siquijorensis). Although the species occur in scrub habitats and nest even in degraded forests, survival of fledglings is probably low owing to predation and collection of eggs by the locals. Given the gaps of information of the species' behavior, possible directions for future studies are also discussed.
Keywords: Bird behavior; Birds -- Feeding and feeds; Bird vocalizations